Key changes in the directive on road infrastructure safety management. - Buczynski, Aleksander (My University, 2019)
The directive 2008/96/EC on Road Infrastructure Safety Management (RISM) defines procedures that were supposed to ensure the safety of the trans-European (TEN-T) road network. The procedures cover different stages and aspects of planning, design and operation of major roads but up until now has almost exclusively focused on the safety of car-occupants. The needs of other road users such as cyclists and pedestrians have often been overlooked in the process, resulting in detrimental infrastructure changes, for example an important cycle route cut off from the rest of the network by a motorway interchange.1 In November 2019, a revision of the directive was published in the Official Journal of the European Union.2 The amendments implemented through the directive (EU) 2019/1936 recognise the need to pay more attention to the safety of cyclists and pedestrians and include many important improvements that ECF has lobbied for in the past two years. The EU Member States now have two years to transpose the updates into national regulations.
Keywords: Europäische Union; Fahrradverkehr; Rechtsänderung; Verkehrssicherheitsprogramm; Vernetzung